2016
DOI: 10.1111/boc.201500090
|View full text |Cite
|
Sign up to set email alerts
|

Efferocytosis of apoptotic human papillomavirus‐positive cervical cancer cells by human primary fibroblasts

Abstract: Our results highlight the cellular and molecular mechanisms of fibroblast-mediated clearance of apoptotic tumour cells. Consequences regarding alternative mechanism of carcinogenesis or tumour progression should be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 70 publications
(129 reference statements)
0
26
0
Order By: Relevance
“…Hermetet et al reported that Macrophages engulf the late but not the early apoptotic populations of papilloma virus-infected cells (Hermetet et al, 2016). In this study, the levels of PtdSer exposure were almost the same in both the early and late apoptotic populations, suggesting involvement of other types of molecules associated with cell death in efferocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hermetet et al reported that Macrophages engulf the late but not the early apoptotic populations of papilloma virus-infected cells (Hermetet et al, 2016). In this study, the levels of PtdSer exposure were almost the same in both the early and late apoptotic populations, suggesting involvement of other types of molecules associated with cell death in efferocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Viral infection induces changes of cell surface molecules related to cell death, and macrophages can recognize these changes and engulf the affected cells. It has been reported that macrophages perform efferocytosis of cells infected with the influenza (Fujimoto et al, 2000; Hashimoto et al, 2007; Shiratsuchi et al, 2000; Watanabe et al, 2005, 2002, 2004; Mukherjee et al, 2017), papilloma (Hermetet et al, 2016), and Drosophila C viruses (Nainu et al, 2015; Nonaka et al, 2017), as well as Lymphocytic choriomeningitis virus (LCMV) (Alatery et al, 2010), and Human Immunodeficiency Virus Type 1 (HIV-1) (Akbar et al, 1994). …”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these results suggest the ability of these large EVs to transform recipient cell [36]. The same group also reported that late ABs are taken up by fibroblasts more efficiently than early ABs, nevertheless the phagocytic activity of these cells remain low compared to those exerted by professional phagocytic cells [37].…”
Section: Mucosal Hpvs and Extracellular Vesiclesmentioning
confidence: 67%
“…Efficient resolution relies on phagocytic engulfment of apoptotic neutrophils by macrophages. Importantly, an early calcium flux in the macrophages is essential for formation of phagocytic cup, internalization of dead cells, and initiation of anti-inflammatory signaling (31)(32)(33)(34). Calcium mobilization is required for transition of proinflammatory macrophages into anti-inflammatory or proresolving ones (35,36).…”
Section: Discussionmentioning
confidence: 99%